Mathematical Description of Energy Transition Scenarios Based on the Latest Technologies and Trends - Askar A. Akaev; Olga I. Davydova (Energies, 2021)
This work, dedicated to a mathematical description of energy transition scenarios, consists of three main parts. The first part describes modern trends and problems of the energy sector. A large number of charts reflecting the latest updates in energy are provided. The COVID-2019 pandemic’s impacts on the energy sector are also included. The second part of the paper is dedicated to the analysis of energy consumption and the structure of the world fuel and energy balance. Furthermore, a detailed description of energy-efficient technologies is given. Being important and low-carbon, hydrogen is discussed, including its advantages and disadvantages. The last part of the work describes the mathematical tool developed by the authors. The high availability of statistical data made it possible to identify parameters used in the algorithm with the least squares method and verify the tool. Performing several not complicated steps of the algorithm, the tool allows calculating the deviation of the average global temperature of the surface atmosphere from preindustrial levels in the 21st century under different scenarios. Using the suggested mathematical description, the optimal scenario that makes it possible to keep global warming at a level below 1.7 °C was found.